2017
DOI: 10.1039/c7ra11496f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, antioxidant activity, and density functional theory study of catechin derivatives

Abstract: Catechin derivatives were synthesized, and their structures were characterized by 1H-NMR, 13C-NMR, and mass spectrometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…Measurement of spin density MEP is a very useful approach for exploring the reactivity and structure-activity relationships of compounds [45][46][47]. A previous study used the MEP to characterize the antioxidant activity of catechin derivatives [48]. To further elucidate the structure-antioxidant activity relationships of DDCDs 1-6, MEP analyses were carried out for the lowest-energy conformers to characterize the similarity and dissimilarity in the electrostatic binding characteristics of the surface of the molecules (Fig.…”
Section: Mepsmentioning
confidence: 99%
“…Measurement of spin density MEP is a very useful approach for exploring the reactivity and structure-activity relationships of compounds [45][46][47]. A previous study used the MEP to characterize the antioxidant activity of catechin derivatives [48]. To further elucidate the structure-antioxidant activity relationships of DDCDs 1-6, MEP analyses were carried out for the lowest-energy conformers to characterize the similarity and dissimilarity in the electrostatic binding characteristics of the surface of the molecules (Fig.…”
Section: Mepsmentioning
confidence: 99%
“…It was previously demonstrated that DFT/B3LYP calculations are a good choice for estimation of the reaction enthalpies as they can provide a fairly accurate agreement between the calculated values and the available experimental data as well as describe reliably the structure-activity relationship for antioxidants with diverse chemical structure at reasonable computational time. [60][61][62][63][64] On the other hand, the use of at least double-zeta basis set, including polarization and diffuse functions, is recommended, 65 therefore the B3LYP//6-311++G(d,p) combination was applied in the present calculations. The results obtained at this computational level allow a useful comparison with earlier studied antioxidants.…”
Section: Computational Study Of the Radical Scavenging Activitymentioning
confidence: 99%
“…GA possesses the most robust antiradical property than Trolox, and hence, in many cases, this molecule is widely used as a reference compound for antioxidant studies. Green tea contains the highest concentration of GA-based compounds responsible for the plant's antioxidant capacity [22,23].…”
Section: Introductionmentioning
confidence: 99%